(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
The aim of present work is to develop a fast disintegrating solid oral dosage form of Metoprolol succinate. The concept of fast dissolving drug delivery system emerged from the desire to provide patient with more conventional means of taking their medication. Problems associated with conventional tablets can be resolved by means of fast dissolving tablets when put on tongue these tablets disintegrate and dissolve rapidly in saliva without need of drinking water. The faster the drug disintegrates in to solution, the quicker the absorption and onset of clinical effect. Preformulation results reveal that the flow properties of the active pharmaceutical ingredient were found to be excellent as per IP limits. To perform drug-polymer compatibility FT-IR studies were carried out and observed that there was no interaction between the APl and excipients. Eight formulations were prepared with varying super disintegrating agent ratios and were found that as the level of super disintegrating agent decreased the drug release rates were found to be increased. Amongst all the formulations, formulation containing CCS (F4) as super disintegrant is fulfilling all the parameters satisfactorily. It has shown excellent in-vitro disintegration, in-vitro dissolution compared to other formulations. The prepared tablets disintegrate within few minutes without need of water; thereby enhance the absorption leading to its increased bioavailability. It was concluded that Fast Disintegrating tablets of Metoprolol can be prepared successfully as it satisfies all the criteria as a dispersible tablet and would be alternative to the currently available conventional tablets. Prepared formulations were stable during 90 days storage period at controlled 40°C and 75%RH.